Remote Intramedullary Hemorrhage in the Thoracic Spinal Cord Secondary to a Perimedullary Arteriovenous Fistula of the Distal End of Conus Medullaris Mimicking Filum Terminale Arteriovenous Fistula: A Case Report - Iampreechakul, Prasert; Liengudom, Anusak; Lertbutsayanukul, Punjama; Siriwimonmas, Somkiet; Pongpech, Sirintara (Asian Journal of Neurosurgery, 2022)
Perimedullary arteriovenous fistulas (PMAVFs) of the conus medullaris are rare and usually manifest with progressive myelopathy secondary to venous congestion resulting from retrograde arterialization of the draining vein into the spinal cord. We present a rare case of conus PMAVF presenting with remote intramedullary spinal cord hemorrhage in the thoracic cord. A 37-year-old woman was transferred to our institute due to sudden severe pain in the left lower leg and weakness of the lower extremities following progressive paresthesia of the lower extremities. Magnetic resonance imaging of the thoracic and lumbosacral spine revealed spinal cord congestion extending from the conus medullaris to the level of T6 with intramedullary hemorrhage at the level of T8–9 on the left side of the spinal cord. There were abnormal serpiginous intradural flow voids along the anterior surface of the spinal cord extending from the level of L2 to the lower cervical with venous varix at the level of T8–9, probably being the source of hemorrhage. Spinal angiography confirmed conus PMAVF at the distal end of the conus medullaris supplied by the sulco-commissural artery arising from the enlarged anterior spinal artery originating from the left T11 intercostal artery with cranial drainage through the dilated anterior spinal vein into the tortuous perimedullary veins up to the lower cervical level. The patient underwent successful endovascular treatment with N-butyl cyanoacrylate and had gradually improved until being ability to walk independently without residual pain of the left lower leg. We speculated that an increased venous flow into a varix may be considered an important risk factor of hemorrhage.
Keywords: type IV spinal cord arteriovenous malformations; perimedullary arteriovenous fistula; conus medullaris; intramedullary hemorrhage; filum terminale arteriovenous fistula